Factors associated with the usage of pharmacy value-added services at public health clinics in the state of Perlis, Malaysia - Soo, Pei Pei; Abdul Latif MF,; Abdul Razak RS,; Syed Azmir SS,; Ng, YH (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
Pharmacy value-added services were developed to make it easier for patients to refill their chronic prescriptions in public health facilities in Malaysia. However, little is known about patients’ awareness, attitudes and practice towards pharmacy value-added services provided by health clinics. This study was conducted to investigate factors associated with the usage of pharmacy value-added services at public health clinics in Perlis, Malaysia. A cross-sectional study was conducted from January to March 2021 at the pharmacy waiting area of all public health clinics in Perlis. All patients (≥18 years old) taking chronic medications and with the need to follow-up at the health clinic in Perlis were recruited in this study using quota sampling. Data was collected using a validated self-administered questionnaire. Descriptive analyses on the usage, awareness and attitudes of respondents were performed, followed by multiple logistic regression. A total of 582 patients responded to this study (response rate, 97.0%). Only 12.9% of respondents used pharmacy value-added services offered by health clinics. Age, gender, ethnicity, education level, occupation, monthly household income, length of stay in Perlis, distance from home to the clinic, total awareness and attitudes scores were factors significantly associated with the practice of pharmacy value-added services after adjusting for other variables (p<0.05). In conclusion, the proportion of patients using pharmacy value-added services at health clinics in Perlis is still low. The study’s findings suggest that a more extensive promotion of pharmacy value-added services is needed to ensure more patients could benefit from these services.